Dampak Permodalan Nasional PNM Mekaar Terhadap Pendapatan Masyarakat Dalam Persfektif Ekonomi Islam - Paul, Wina; Syaripudin, Enceng Iip; Furkony, Deni Konkon (Jurnal Hukum Ekonomi Syariah, 2023)
The Madani National Capital Mekaar Program (PNM) is strengthened by business assistance activities and carried out in groups. Not only disbursing credit as capital for small businesses, but the Mekaar Program also provides coaching and management services. The purpose of this study is to determine 1) the mechanism of PNM Mekaar 2) community income 3) the impact of PNM Mekaar on community income. The type of research used is a quantitative approach with a correlative descriptive method. Data collection techniques used in the form of questionnaires, observations, interviews, and documentation. The results showed that 1) the Mekaar National Capital Mechanism (PNM) (Variable X) was shown with an average score of 3.98 including the high category because it was in the range of 3.40 – 4.19. 2) Community income is shown with an average score of 3.06 including the medium category because it is in the range of 2.60 – 3.39. Meanwhile, after conducting research, people's income turned out to decrease after borrowing from PNM Mekaar. 3) The Impact of Madani National Capital (PNM) Mekaar (Variable X) on Community Income (Variable Y) Based on the calculation of the Spearman rank correlation analysis, it shows a correlation coefficient price of 0.581, the figure is in the value interval of 0.400 – 0.599, meaning that the correlation is qualified sufficiently.